2020
DOI: 10.1080/14767058.2020.1754395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus and its determinants among pregnant women in Beijing

Abstract: Other minorities 1000 213 21.30 (18.76-23.84) 1.00 reference 1.00 reference Maternal age(years) ≤25 4330 721 16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The eastern and southern parts of China, characterized by relatively better economic development, have a much higher prevalence of GDM. A study according to 27,119 pregnant women in Tongzhou district of Beijing during 2013–2018 showed that the overall prevalence of GDM was 24.24% according to the IADPSG criteria [ 21 ]. The higher prevalence in Tongzhou district might due to the traditional dietary and lifestyle of individuals in this suburb area of Beijing, as they still lack of knowledge on how to keep a balanced diet and healthy lifestyle during pregnancy, which raised an urgent need for education on healthy diet and lifestyle around China.…”
Section: Prevalence Of Gdm In Chinamentioning
confidence: 99%
“…The eastern and southern parts of China, characterized by relatively better economic development, have a much higher prevalence of GDM. A study according to 27,119 pregnant women in Tongzhou district of Beijing during 2013–2018 showed that the overall prevalence of GDM was 24.24% according to the IADPSG criteria [ 21 ]. The higher prevalence in Tongzhou district might due to the traditional dietary and lifestyle of individuals in this suburb area of Beijing, as they still lack of knowledge on how to keep a balanced diet and healthy lifestyle during pregnancy, which raised an urgent need for education on healthy diet and lifestyle around China.…”
Section: Prevalence Of Gdm In Chinamentioning
confidence: 99%
“…Of note, the incidence of GDM in China displayed substantial differences across cities and regions. For example, in the Tongzhou district of Beijing, the overall prevalence of GDM was 24.24%, and the trend increased from 21.63% to 25.49% during 2013-2018 ( 9 ). In the same period, a population-based study in Xiamen reported that the rate of GDM ranged from 15.5% to 19.9% ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 Factors including obesity and a family history of diabetes mellitus have been reported to associate with GDM. 6,[9][10][11] Due to the relevancy of carbohydrate and lipid metabolism pathways, the association between serum lipid profiles and GDM has recently gained attention. 12,13 A systematic review by Ryckman et al found significantly elevated serum triglyceride (TG) levels in women with GDM across all three trimesters of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In current clinical practice, GDM is usually diagnosed based on results of the 75 g two‐hour oral glucose tolerance test (OGTT) performed between 24 and 28 gestational weeks, which leads to a very limited time for treatment before delivery, 7 Studies have found that early recognition of pregnant women at high risk of GDM would allow for appropriate interventions and the improvement of pregnancy outcomes 8 . Factors including obesity and a family history of diabetes mellitus have been reported to associate with GDM 6,9‐11 . Due to the relevancy of carbohydrate and lipid metabolism pathways, the association between serum lipid profiles and GDM has recently gained attention 12,13 .…”
Section: Introductionmentioning
confidence: 99%